PEMIKIRAN FILOSOFIS AL-FARABI TENTANG PENDIDIKAN ISLAM RELEVANSINYA DENGAN PENDIDIKAN PESANTREN - Lutfi Hakim (Jurnal Ilmu Pendidikan Islam, 2021)
Education is a media to obtain values, knowledge and practical skills for individuals in a certain period and culture whose final purpose is to lead those individuals to perfection. According to al-Farabi, a human being was created to achieve perfection. Meanwhile, the highest perfection is happiness. As stated by al-Farabi, perfect humans are those who have known the virtue theoretically and practiced it in practical life. Education must be able to create ideal humans who are capable to embody knowledge in the reality of life. For now, the most appropriate educational model as proposed by al-Farabi is Pesantren or Islamic boarding school education. Keywords: Al-Farabi, Education, Character, Islamic Boarding School.